Pengaruh Dance Movement Therapy terhadap Kualitas Tidur pada Lansia di Dukuh Garen Desa Pandeyan Kecamatan Ngemplak, Boyolali - Fitriani, Rizka; Sri Wahyuni, Endang (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Elderly people can experience various health problems, one of which is difficulty sleeping. One way that can be used to overcome sleep disorders is Dance Movement Therapy which can improve the quality of elderly sleep. Objectives: This research aims to determine the difference in sleep quality before and after being given Dance Movement Therapy to the elderly in Dukuh Garen, Pandeyan Village, Ngemplak District, Boyolali. Methods: This research is quantitative research. This research method uses pre-experimental with a one group pre-test post-test design approach. The sampling technique is purposive sampling. The instrument used is the PSQI (Pittsburgh Sleep Quality Index). Research data was analyzed using the Wilcoxon signed rank test. Results: The results of this study were dominated by 18 (90%) seniors aged 60-69 years, 19 (95%) female seniors, 20 (100%) seniors who all lived with their families, 13 (100%) seniors who still had a partner ( 65%), and the elderly who do not work are 14 (70%). In the Wilcoxon test, the value obtained was p=0.000 (p<0.05) where there was a difference in sleep quality in the elderly before and after being given Dance Movement Therapy. Conclusion: This research shows that there is an influence of Dance Movement Therapy on sleep quality in the elderly in Dukuh Garen, Pandeyan Village, Ngemplak District, Boyolali. Keywords: Dance Movemnet Therapy, Sleep Quality, Elderly